Password authentication scheme based on smart card and QR code - Mushtaq Hasson; Ali A. Yassin; Abdulla J. Yassin; Abdullah Mohammed Rashid; Aqeel A. Yaseen; Hamid Alasadi (Institute of Advanced Engineering and Science, 2021)
As a hopeful computing paradigm, cloud services are obtainable to end users based on pay-as-you-go service. Security is represented one of the vital issues for the extended adoption of cloud computing, with the object of accessing several cloud service providers, applications, and services by using anonymity features to authenticate the user. We present a good authentication scheme based on quick response (QR) code and smart card. Furthermore, our proposed scheme has several crucial merits such as key management, mutual authentication, one-time password, user anonymity, freely chosen password, secure password changes, and revocation by using QR code. The security of proposed scheme depends on crypto-hash function, QR-code validation, and smart card. Moreover, we view that our proposed scheme can resist numerous malicious attacks and are more appropriate for practical applications than other previous works. The proposed scheme has proved as a strong mutual authentication based on burrows-abadi-needham (BAN) logic and security analysis. Furthermore, our proposed scheme has good results compared with related work.